Co-infecção por patógenos transmitidos por artrópodes em gatos domésticos - André, Marcos Rogério [UNESP]; Filgueira, Kilder Dantas; Calchi, Ana Cláudia [UNESP]; de Sousa, Keyla Carstens Marques [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; Medeiros, Vitor Brasil; Ximenes, Poliana Araújo; Lelis, Vana Cristina Nunes Gadelha; de Meireles, Maria Vanuza Nunes; Machado, Rosangela Zacarias [UNESP] (FapUNIFESP (SciELO), 2017)
The role of several feline vector-borne pathogens (FVBP) as a cause of disease in cats has not been clearly determined. In fact, with the exception of Bartonella spp. and hemoplasmas, FVBP in cats has not been clearly determined in Brazil yet. The present study aimed at identifying, by using molecular methods, the presence of FVBP in three cats showing non-specific clinical signs and inclusions suggestive of hemoparasites in blood smears. Cytauxzoon felis, ‘Candidatus Mycoplasma haemominutum’, Ehrlichia sp. closely related to Ehrlichia canis, and Anaplasma sp. closely related to Anaplasma phagocytophilum were detected in blood samples from two out of three sampled cats. Both cats positive for multiple FVBP did not show hematological and biochemical abnormalities. The present work emphasizes the need for molecular confirmation of co-infection by multiple FVBP in cats presenting non-specific clinical signs and inclusions resembling hemoparasites in blood smears.
Co-infection with arthropod-borne pathogens in domestic cats
Keywords: Anaplasma; Cytauxzoon; Ehrlichia; Feline; Mycoplasma